Effect of high blood pressure on thyroid and lipid profile of pregnant women - Gill, Gurpreet Kaur; Kaur, Mandeep; Singh, Partapbir; Kataria, Juhi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Hypertension is common medical problem encountered during pregnancy, complicating up to 10% pregnancies. Hypertension is defined as the systolic blood pressure ≤140 mmHg and a diastolic blood pressure ≥90 mmHg on two separate measurements at least 4-6 hours apart. During pregnancy thyroid demand changes with increased iodine uptake and synthesis of thyroid hormone. Serum from pre-eclamptic women had both a higher ratio of free fatty acid to albumin and increase up take of free fatty acids, which are further esterified to triglyceride. The aim of the present study was to evaluate thyroid hormone, lipid profile and urine albumin in hypertensive pregnant women and its comparison with normotensive pregnant women Methods: Total 90 samples were collected from Beri Maternity Hospital and Civil Hospital, Amritsar. Blood samples were analysed for biochemical parameters viz. lipid profile and thyroid profile. Urine samples were also analysed for presence of albumin. Results: From the study it has been revealed that thyroid stimulating hormone (TSH) levels increased in hypertensive pregnant women mean (4.26±1.1µ/ml). The total cholesterol (234.56±14.2mg/dl), triglyceride (138±16.96mg/dl), HDL (50.7±7.4mg/dl), LDL (156.2±17.11mg/dl) and VLDL (27.7±3mg/dl) was found altered in hypertensive pregnancy as compared to normotensive pregnancy. The albumin excretion was seen in 13.3% hypertensive pregnancies. Conclusions: TSH were elevated in hypertensive pregnant women due to the effects of estrogen. Among all the parameters of lipid profile, total cholesterol, TG, LDL and VLDL has been increased significantly in hypertensive pregnant women as compared to normotensive pregnant women due endothelial dysfunction.